Research on a New Nitrogen Foam Fracturing Fluid System and its Application in Tight Gas - Long, Lieqian; Du, Junshan; Yang, Bing; Li, Jun (International Journal of Natural Resources and Environmental Studies, 2025)
Sichuan XX block belongs to the "low porosity, low permeability, low pressure" gas reservoir, and the effect of conventional fracturing is ignored, and the nitrogen foam fracturing process is recommended after analysis. After the optimization and evaluation of laboratory experiments, a nitrogen foam fracturing fluid system suitable for Sichuan block was formed, and the results showed that the system had the characteristics of low damage, low filtration loss and strong sand carrying capacity compared with the traditional fracturing fluid. The pilot test of the nitrogen foam fracturing fluid system was carried out in this block, and compared with the conventional guanidine gum fracturing fluid construction wells in the same block, it has obvious advantages in terms of construction pressure, liquid efficiency, sand suspension capacity, and flowback rate. The gas time is significantly shortened, and the daily gas production is significantly increased, indicating that the new nitrogen foam fracturing fluid system has achieved good fracturing results.